The role of communication and knowledge management as evidenced by HCP vaccination programs in the Netherlands, Germany and Italy: Possible suggestions for medical translators - Ross, Dolores; Magris, Marella (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
The main objective of this paper is to study mediation aspects in health communication, particularly in the field of HPV (Human Papilloma Virus) vaccination in three countries: the Netherlands, Germany and Italy. As an additional research question we will try to understand the extent to which medical translation and medical writing can be integrated, in the perspective of a greater recognition of the translators’ role as knowledge managers. After comparing the quality level of public service communication in the three countries, we will discuss outcome and social-political conditions of the HPV campaigns. Considering the growing importance of communication professionals in institutional health settings, we will explore possible implications for the social role of medical translators and raise the question of the extent to which translators of medical information material may be allowed to stretch the boundaries of translation and operate more far-reaching choices concerning medical writing. The relevance of this study is to gain insight into health communication in three different language communities and to consider implications for medical translator practice and training.